TIPS MEMILIH DAN MENYIMPAN TELUR YANG AMAN UNTUK DIKONSUSMI - Desmond T.R. Hurek; Diana M. Rihi; Poppy S. Pello; Venansia N. Beti; Maria M. Moi; Mesa J. N. Boru; Rizky Y. Manafe; Maria Veronika Dua Eni Parera; Nadya D. Kale; Novalino H. G. Kallau; Annytha I. R. Detha; Diana Agustiani Wuri; Larry R. W. Toha (Jurnal Media Tropika, 2021)
Eggs are perfect foodstuffs because they contain nutrients such as protein, fat, vitamins, and minerals in sufficient quantities. Under certain conditions, the complete nutritional content in eggs can be a good growth medium for microorganisms. It is important to educate the community about how to differentiate egg quality and how to store eggs properly so that people can choose and get eggs of good quality in the long term. The benefit is that they can be more careful in choosing the eggs to buy, and know-how to store eggs properly so that the egg's shelf life can last longer. This education was carried out online during the Covid-19 pandemic Work From Home (WFH) period using the Zoom meet application. The participants in this counseling consisted of housewives and students.